2021
DOI: 10.1088/1742-6596/1810/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Gamification design for high school student with unstable internet connection during covid-19 pandemic

Abstract: Balinese society is a unique combination of traditions, culture, religion, values and moral values with a background of beautiful nature. As the centre of this combination is the Hindu Religion, which is the faith of the majority thus it is taught to students from elemntary school to high school. However, the Covid-19 pandemic, the teaching of Hindu religion has been switched to online leanring, at it poses challenges, such as lack of technological skill on the part of the teachers, unstable internet access, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…It is interesting that the mechanics of rewards that encourage engagement, attention, submission of high-quality assignments, and emotion can positively affect the performance of students in both types of careers. This matches what was found by [40,43,44]. In this regard, a didactic design based on gamification can be a positive tool for teachers of virtual environments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is interesting that the mechanics of rewards that encourage engagement, attention, submission of high-quality assignments, and emotion can positively affect the performance of students in both types of careers. This matches what was found by [40,43,44]. In this regard, a didactic design based on gamification can be a positive tool for teachers of virtual environments.…”
Section: Discussionsupporting
confidence: 89%
“…Undergraduates earned the Stark badge when they answered a more challenging question or placed first in a Kahoot. Gamification based on a mechanic of rewards has proven to be a useful teaching tool to engage students, particularly in online environments [21,[40][41][42], and also those who live inside an enclosed academic environment [43,44]. In this regard, this study analyzed the performance of university students, one group from the Engineering school and the other from the Economics and Social Sciences school.…”
mentioning
confidence: 99%
“…These animation and interactive video materials produced higher learners' motivation when using distance learning [24]. In recent years, gamification has also emerged as an efficient pedagogical strategy to increase students' motivation and involvement [25,26]. It was used also during COVID-19, and it allowed students to interact while having fun experiences, especially in STEM (science, technology, engineering and mathematics) disciplines that need laboratories [27].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, some students had difficulties understanding the material delivered online; primary school students sometimes felt bored and were less active and interested in participating during the distance learning process [12,13]. For this purpose, some studies suggested the use of interactive and multimedia materials (animations, images, games) to increase students' motivation [14,15]. Virtual-reality technology and gaming tools can be effectively used to achieve a high level of engagement and to foster attention, interaction, and collaboration among students [16].…”
Section: Students' Engagement and Motivationmentioning
confidence: 99%